Animal Welfare Policies and their Effect on Livestock Productivity and Trade - Nkatekho, Blessings (International Journal of Livestock Policy, 2024)
Purpose: This study sought to explore animal welfare policies and their effect on livestock productivity and trade. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to animal welfare policies and their effect on livestock productivity and trade. Preliminary empirical review revealed that implementing robust animal welfare policies significantly improved livestock productivity and enhanced marketability and trade. Improved welfare standards led to better animal health, reduced stress, and increased yields, translating to higher profitability for producers. Furthermore, products from high-welfare farms gained access to premium markets and fetched higher prices. However, the initial costs of adopting these standards and the need for more comprehensive studies on long-term economic impacts were identified as challenges. The study recommended policy support, financial incentives, and education to promote widespread adoption of high welfare practices Unique Contribution to Theory, Practice and Policy: Theory of Planned Behavior (TPB), Resource-Based View (RBV) and Stakeholder Theory may be used to anchor future studies on animal welfare policies. The study recommended integrating animal welfare into theoretical frameworks like Resource-Based View and Stakeholder Theory, emphasizing its strategic value and ethical importance. Practically, it suggested that livestock producers adopt comprehensive welfare practices to improve productivity and profitability. Policy recommendations included financial incentives and robust enforcement to support high welfare standards. It also highlighted the need for education and training programs for farmers and public awareness campaigns to drive demand for welfare-friendly products. Further research was advised to explore long-term economic impacts and the integration of welfare with sustainability frameworks.